2016
DOI: 10.5812/aapm.38337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Open and Closed Endotracheal Suctioning Methods on Pain and Agitation in Medical ICU Patients: A Clinical Trial

Abstract: BackgroundEndotracheal suctioning is a necessary procedure practiced by nurses in intensive care units to remove lung secretions. This procedure leads to higher oxygenation levels and reduced breathing difficulties. It also prevents atelectasis, pulmonary infections, and the accumulation of secretions.ObjectivesThe present study aims to compare the effectiveness of open and closed endotracheal suction tube systems on pain and agitation in patients under mechanical ventilation.MethodsA randomized controlled cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 28 publications
4
36
2
8
Order By: Relevance
“…In severe cases, it causes a decrease in blood oxygen saturation and an increase in ICP, producing discomfort, and even causing pain [4-17, 36-40]. Lucchini and coworkers [37] documented that patients subjected to mechanical ventilation recalled that during their stay in the ICU, ES was the most painful process, with 99% of them reporting painful experience during ES [36][37][38][39]. The current study demonstrated that the effect of ES was accomplished successfully in both the experimental and the control group, but the two groups differed in the grade of choking cough response.…”
Section: Propofol Sedation Ensures Es Effect and Reduces Painmentioning
confidence: 99%
“…In severe cases, it causes a decrease in blood oxygen saturation and an increase in ICP, producing discomfort, and even causing pain [4-17, 36-40]. Lucchini and coworkers [37] documented that patients subjected to mechanical ventilation recalled that during their stay in the ICU, ES was the most painful process, with 99% of them reporting painful experience during ES [36][37][38][39]. The current study demonstrated that the effect of ES was accomplished successfully in both the experimental and the control group, but the two groups differed in the grade of choking cough response.…”
Section: Propofol Sedation Ensures Es Effect and Reduces Painmentioning
confidence: 99%
“…In severe cases, it causes a decrease in blood oxygen saturation and an increase in ICP, producing discomfort and even causing pain [4][5][6][7][8][9][10][11][12][13][14][15][16][17][36][37][38][39][40]. Lucchini and coworkers [37] documented that patients subjected to mechanical ventilation recalled that during their stay in the ICU, ES was the most painful process, with 99% of them reporting painful experience during ES [36][37][38][39]. The current study demonstrated that the effect of ES was accomplished successfully in both the experimental and the control group, but the two groups differed in the grade of choking cough response.…”
Section: Propofol Sedation Ensures Es Effect and Reduces Painmentioning
confidence: 99%
“…Penggunaan Dalam penelitian sebelumnya sekitar 46,8% responden mengalami penurunan saturasi oksigen 6,5% karena tindakan suction 15 . Sebelum dilakukan suction tanda-tanda vital dalam batas normal, observasi setelah suction menunjukkan peningkatan tanda-tanda vital (terutama denyut jantung dan frekuensi pernafasan) akibat adanya sekresi pada saluran nafas (indikasi suction) yang menyebabkan penurunan saturasi oksigen 16,17 . Tekanan 140 mmHg lebih efektif daripada tekanan 130 mmHg, dan efektif menghilangkan sekret secara keseluruhan sehingga meningkatkan pasokan oksigen perifer saturasi oksigen dengan meningkatnya pasokan oksigen ke perangkat yang efektif dan meningkatkan tingkat SpO2.…”
Section: Monitoringunclassified